Using Online Learning Environments to Address Digital Literacy Competencies of Construction Management Graduates (International Conference on Computers in Education, 2020)
Digitalization has become popular across various industries including construction. Construction industry involves unique outputs, complex processes and multi-disciplinary engagements. Digitization has introduced in the industry from electronic documents, email communication to automation and concepts such as Building Information Modelling (BIM). Construction professionals should possess sets of skills to cope with complex nature in the industry whilst conquering this modern digital era. United Nations Educational, Scientific and Cultural Organization (UNESCO) has proposed a set of digital literacy competencies for youth and adults in their ‘Digital Literacy Global Framework’. Meanwhile, some professional bodies in construction also have acknowledged Information and Communications Technology (ICT) skills as core to their professionals. In this vein, digital literacy will be a competitive advantage for construction management graduates. Digital literacy practices are not emerging spontaneously but, education plays an important role in this context. Learning Management Systems (LMS) are widespread among higher education providers for both face-to-face and online offerings. LMS are tailored to cater various pedagogical strategies and can also be used to enrich digital literacy of students. This paper maps how the digital literacy competences proposed by UNESCO are addressed with online activities and resources used in first year courses in a construction management degree program operating in an online educational environment in Australia facilitated through Moodle Learning Management System. The core competencies recognized by major construction professional bodies were considered as the ‘Career-related competences’ in the UNESCO framework. The paper also presents which of the online activities are mostly implemented and engaged in the selected courses and which of the core competencies are mostly addressed. Findings suggest ‘Assignment’, ‘Forum’ and ‘Quiz’ as the mostly implemented and engaged activities, whereas ‘Glossary’ activity with less implementation but, higher engagement so, with a higher potential of addressing digital competencies. Information and data literacy, communication and collaboration, digital content creation and career-related competency of using standard computer packages are the mostly addressed competencies.